Property valuation by multiple criteria methods/Nekilnojamojo turto vertinimas daugiakriteriniu metodu - Malienė, Vida; Zavadskas, Edmundas K.; Kaklauskas, Artūras; Raslanas, Saulius (Journal of Civil Engineering and Management, 1999)
Multiple criteria valuation methods are widely used in real estate valuation all over the world. In USA, UK and other countries these methods are part of techniques based on comparative and reinstatement values as well as on income of use. They are used in valuating various property characteristics, ie its location or obsolescence degree. In Germany, however, multiple criteria valuation technique refers to a separate group of property valuation methods applied when market data are unavailable or insufficient (ie purchasing, selling or renting prices are not known). The above methods have been used for real estate valuation since 1976. Dr. H. E. Auerhammer [1] was the first to apply these approaches to solving real estate valuation problem caused by the scarcity of market data. These methods supplemented with systems of criteria developed by other authors were later applied to particular cases when three major commonly used property valuation methods could not be applied. Thus, K. Gablenz [2] suggests using the method described in assessing plots intended for agriculture, while B. Bischoff [3] offers to use it for determining the investments into plots. R. Vogel [4] thinks that the approach may be used for determining the approximate value of land, whereas G. Sommer and P. Zimmermann [5] and Piehler [6] developed a system of criteria to be used as a part of the method described in determining the differences between the value of quantitative and qualitative characteristics of an object and its market value. T. Gierardy and R. Moeckel [7] described the advantages and disadvantages of methods based on multiple criteria analysis. The above methods are widely used in Germany for property valuation, the peak of their application being associated with the unification of East and West Germany in 1990 [8]. Multiple criteria analysis presented in this paper for property valuation may be used to the advantage of various interested parties (see Fig 1). The representatives of various parties including appraisers, buyers, sellers and investors may use it for their particular purposes: – appraiser may apply this method to real estate value analysis for determining the market, use and other values of real estate being mortgaged, ensured, privatised, divided or nationalised; – investor may rely on it for more efficient use of this property; – buyer may use it for choosing property which would satisfy his personal needs to the best advantage; – seller has to determine the market price of his property that would ensure its competitive ability on the market.To satisfy all the needs described multiple criteria valuation method presented in the paper may be successfully used. To show its efficiency the solution of a sample problem, representing a real case is provided.Article in Lithuanian.First Published Online: 26 Jul 2012